2019
DOI: 10.1097/md.0000000000017991
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of laparoscopic gastrectomy in obese patients with gastric cancer

Abstract: The present study aimed to investigate the safety and short-term outcome of laparoscopy-assisted distal radical gastrectomy in treating gastric cancer among obese patients. Perioperative outcomes were compared between 67 gastric cancer patients with a body mass index (BMI) ≥25 kg/m2 (obese group) and 198 ones with BMI <25 kg/m2 (non-obese group). All the cases underwent laparoscopic radical resection between April 2009 and October 2013. The value of BMI was 27.3 ± 2.67 kg/m2 in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Some researchers demonstrated that obesity is an important risk factor for postoperative complications, and the rate of postoperative complication in obese patients is higher than that in patients with normal weight [11][12][13][14]. However, some other researchers disagreed with that and pointed out that obesity did not affect postoperative complications in some surgery [15][16][17][18]. So far, whether a higher BMI can compromise surgical outcomes via subxiphoid uniportal VATS in patients with AMT is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers demonstrated that obesity is an important risk factor for postoperative complications, and the rate of postoperative complication in obese patients is higher than that in patients with normal weight [11][12][13][14]. However, some other researchers disagreed with that and pointed out that obesity did not affect postoperative complications in some surgery [15][16][17][18]. So far, whether a higher BMI can compromise surgical outcomes via subxiphoid uniportal VATS in patients with AMT is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, China has the largest number of overweight people (more than 89.6 million in 2014) 21 . Problems related to obesity have attracted an increasing amount of attention from surgical specialists since a large amount of adipose tissue in the abdominal wall and the abdominal cavity greatly increases the difficulty of exposing the operative field in laparotomy 4 . Studies also indicate that, compared with non-obese patients, obese patients experience significantly longer operation times, more intraoperative blood loss, and are more likely to develop postoperative complications after abdominal operation 4 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Problems related to obesity have attracted an increasing amount of attention from surgical specialists since a large amount of adipose tissue in the abdominal wall and the abdominal cavity greatly increases the difficulty of exposing the operative field in laparotomy [4]. Studies also indicate that, compared with non-obese patients, obese patients experience significantly longer operation times, more intraoperative blood loss, and are more likely to develop postoperative complications after abdominal operation [4,20]. Considering the priority of VO over BMI in several studies [11,20], we used CT-based-VFA for determining VO in this study and observed a high incidence of VO in patients with GC (42.61%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations